Effects of a lag schedule of reinforcement with progressive time delay on topographical mand variability in children with autism. (3rd April 2018) - Silbaugh, Bryant C.; Falcomata, Terry S.; Ferguson, Raechal H.
ABSTRACT: Objective : Evaluate the effects of a Lag 1 schedule of reinforcement and progressive time delay (TD) on topographical mand variability in children with autism. Methods : Using single-subject design methodology, a multiple baseline across behaviors with embedded reversal design was employed. During Lag 0, reinforcement was delivered contingent on any independent instances of manding. During Lag 1 + TD, prompts were faded and reinforcement was delivered contingent on independent or prompted variant mand topographies. Results : Higher levels of topographical mand variability were observed during Lag 1 + TD for both participants. Conclusions : A Lag 1 schedule of reinforcement with progressive TD increased variability across functionally equivalent vocal mand topographies for both participants. This finding extends prior literature by providing a novel model for studying reinforced mand variability in children, and by demonstrating how practitioners could use prompts and differential reinforcement to increase topographical mand variability in children with autism.